PTU-125 Improving quality and reducing frequency of hospital care for alcohol-use disorder patients: a multi-disciplinary-team approach. (8th June 2018) - Owens, Lynn; Kullu, Cecil; Byrne, David; Lewis, Elaine; Patterson, Kev; Richardson, Paul
Abstract : Introduction: Patients with alcohol dependence often have complex health and social care needs resulting in frequent attendance at hospital. All too often care is aimed at optimising medical treatment of presenting conditions with little attention to, and planning for mitigation of causes, frequently exacerbated by non-medical problems. This failure to address the wider determinants of health often leads to a cycle of readmission. Therefore we aimed to improve the overall management of this patient group by bringing together a multidisciplinary team (MDT) to develop personalised multi-service, multi-professional care pathways. Methods: We developed a core multidisciplinary group with representation from our hospital hepatology team, our alcohol service, liaison psychiatry, occupational therapy, and our partners in primary care and homeless services. Other professionals and services were invited to the MDT meeting based on individual patient needs; this included the patient and or family and carers as appropriate. The purpose of this group was to develop a bespoke pathway of care with all current and future care providers, and foster an atmosphere for collaboration and mutual support. Our patients were often being cared for by multiple services, however much of this work was happening in isolation and was at times conflicting. Importantly, the patients were unclear where to go for what, and were utilising the ED as a failsafe when they were troubled. Results: MDT facilitated communication between services, professionals and the patient. This helped us provide planned rather than reactive care. For our 46 patients who have been presented at MDT, at six month follow-up we were able to demonstrate a significant reduction in hospital attendance and admission, resulting in ~120 less admissions and ~434 ED attendances across the acute trust; this equates to a s aving within the last 6 months of an estimated £63 600 on ED attendance alone. Conclusions: MDT meetings are a familiar element of system delivery within acute hospitals. What is unique about our approach, and has resulted in significant quality improvement is that we invested time building relationships with people from organisations not traditionally included in acute hospital care planning. This included those working in homeless shelters, probation services, voluntary agencies, families and patients. We believe our success could provide the confidence for other acute care teams across the NHS to replicate our model.